Coping With COVID: Does Prior Military Service Play a Role for Vietnam Veterans?. (17th December 2021) - Stellman, Jeanne; Stellman, Steven; Kaiser, Anica; Spiro, Avron; Smith, Brian
Abstract: We investigated the impact of earlier military combat on ability to cope with the COVID-19 pandemic in 379 male Vietnam veterans who responded to surveys in 1984, 1998, and 2020. Combat exposure was scored with a validated scale, contrasting lowest tertile (8-15) vs. medium/high (16-40). About one-fourth of veterans (26%) reported that their military experience made it easier to cope with the pandemic, while over half (59%) said it had no effect. Medium/high-combat veterans were more likely to report that their military experience made coping easier (OR = 1.8, p = 0.03), but were less likely to report no effect of service on their coping than low-combat veterans (OR = 0.40, p<0.001). All 19 respondents (5%) who said military experience made coping more difficult were medium/high combat veterans. Military experience, and combat particularly, affected many of these veterans' ability to cope with the pandemic decades after their service.